RESERVOIR CHARACTERIZATION IN UPPER RED BED FORMATION INTERVAL, NORTH AMAN SUBBASIN, CENTRAL SUMATRA BASIN, RIAU - Rifky Fauzi, Muhammad
The Aman Utara Subbasin is one of the largest hydrocarbon-producing subbasins located in the Central Sumatra Basin, where the focus of this research is to characterize the reservoir in the Upper Red Bed Formation interval. Reservoir characterization is needed to understand the geological conditions below the surface and to determine the prospects of available hydrocarbon resources. Thus, this research aims to understand the regional geology and geology of the research area, precisely in the Aman Utara Subbasin. In addition, this research aims to determine the reservoir characteristics qualitatively in the form of facies, stratigraphic correlation, and reservoir geometry, as well as reservoir characterization quantitatively which includes reservoir properties. The data used in this research are wireline logs, one checkshot data, three-dimensional seismic lines, and side-wall core data from drill cuttings in one research well. The methods used in this research include facies analysis, petrophysical analysis, subsurface mapping, and determination of the depth interval of the net pay zone hydrocarbon. Through facies and depositional environtment analysis, it is concluded that the reservoir in the Upper Red Bed Formation in the research location was deposited in a braided river environment with architectural elements in the form of fluvial channels and overbank fines. Petrophysical analysis shows that the reservoir has average petrophysical properties; shale volume 0.16 - 0.22, effective porosity 0.12 - 0.15, and effective water saturation 0.79 - 0.96. A net hydrocarbon pay zone is found in well RF-1 with a thickness of 9 meter, while the other wells are nonprospective for hydrocarbons.